Low PTH Levels in Adolescents With Anorexia Nervosa - Lenherr-Taube, Nina; Trajcevski, Karin; Sochett, Etienne; Katzman, Debra K. (Frontiers in Pediatrics, 2020)
Introduction: Patients with anorexia nervosa (AN) experience medical complications including impaired bone metabolism, increased fracture rate, kidney stones and chronic renal failure. However, the mechanisms of such complications are not fully understood. Healthy adolescents have been shown to have higher PTH levels when compared with pre-pubertal children and adults. Given the importance of central measures of calcium and vitamin D metabolism in bone and kidney health, 25-hydroxyvitamin D (25OHD) and parathyroid hormone (PTH) have been extensively investigated in patients with AN, however none of the previous studies accounted for age-specific reference ranges for PTH. The aim of this study was to investigate central measures of calcium and vitamin D metabolism in adolescents with newly diagnosed AN using age-specific reference ranges and to determine whether any significant abnormalities required further study. Methods: This was a cross-sectional study of 61 adolescents (mean age = aged 15.2 ± 1.56 years) with newly diagnosed AN, referred to a tertiary center over a period of two years. Demographic, auxiological, and nutrient (vitamin D and calcium) intake data was obtained. Central measures of calcium and vitamin D metabolism in blood and urine were investigated. PTH results were compared with age-specific reference ranges from the Canadian Laboratory Initiative on Paediatric Reference Intervals (CALIPER). Descriptive statistics and correlation analysis were performed. Results: Low PTH levels were observed in 35% of the cohort. Overall, serum calcium, phosphate and 25OHD were within the reference range. Using loess curves, PTH had a significant negative and non-linear correlation with 25OHD with an inflection point at a 25OHD level of 100 nmol/l, above which the association was no longer present. Correlation analysis did not show a significant association between PTH and total or corrected serum calcium, urine calcium/creatinine (Ca/Cr) ratio, total dietary calcium intake, magnesium or Tanner staging. Conclusion: PTH levels were reduced in approximately a third of adolescents with AN. This observation has not been reported given the universal usage of reference ranges that covers all ages. This finding may unmask a potential role for reduced PTH levels in the pathogenesis of kidney stones and bone phenotype in patients with AN.